Analysis of the Influence of Control Strategy and Heating Loads on the Performance of Hybrid Heat Pump Systems for Residential Buildings - Erica Roccatello; Alessandro Prada; Paolo Baggio; Marco Baratieri (Energies, 2022)
Air-to-water heat pumps (HPs) are widely installed in new buildings; however, they face performance degradation with high temperature emission systems, which is typical of existing buildings, or during domestic hot water (DHW) production. Hybrid systems (HSs), composed by air-to-water HPs and gas-fired boilers, can mitigate these issues by increasing the overall system efficiency. HS performance is strictly dependent on the configuration and control management of the system itself. Moreover, the building and heating plant also have a strong influence. This study presents an overview of the application of HSs that considers both space heating (SH) and DHW production, by comparing the primary energy (PE) consumption obtained by dynamic simulations. Different climates, building typologies, and DHW withdrawal profiles are used to extend the results’ validity. Additionally, several HS control strategies were implemented and compared. The results show a PE savings ranging from 5% to 22% depending on the control strategy and the external parameters applied in the simulation. The comparison of the control strategies shows that the most efficient strategies are the ones maximizing heat pump utilization. The dependence of PE savings of HS on COP values is highlighted, and a correlation is presented to provide designers with guidance on the applicability of HSs.